Cytotoxic properties of radionuclide-conjugated Cetuximab without and in combination with external irradiation in head and neck cancer cells in vitro. (August 2014) - Eke, Iris; Ingargiola, Mirjam; Förster, Claudia; Kunz-Schughart, Leoni A.; Baumann, Michael; Runge, Roswitha; Freudenberg, Robert; Kotzerke, Jörg; Heldt, Jan-Martin; Pietzsch, Hans-Jürgen; Steinbach, Jörg; Cordes, Nils
Abstract Purpose: Epidermal growth factor receptor (EGFR) is critically involved in progression and therapy resistance of squamous cell carcinoma (SCC). Albeit EGFR targeting could improve the effect of radiotherapy on patients' outcome, the clinical results failed to meet expectations from preclinical studies. In this work, we evaluated the potential of the radionuclide Yttrium-90 (90Y) bound to Cetuximab (90Y-Cetuximab) as novel targeting approach for SCC cells in vitro. Materials and methods: FaDu and A431 cell lines were used. EGFR subcellular localization, clonogenic survival, radiation-induced γH2AX foci and EGFR signaling were examined. Cells were treated with DTPA, DTPA-Cetuximab, 90Y and 90Y-Cetuximab alone or in combination with external X-ray irradiation. Results: Dose- and cell line-dependently, 90Y-Cetuximab mediated a significant reduction in clonogenicity relative to unbound 90Y. Combined 2-Gy external radiation plus 2-Gy equivalent dose of 90Y-Cetuximab was more effective than equivalent doses of 90Y and X-ray radiation. Analogous effects were observed in the number of residual radiation-induced foci. Additionally, EGFR, ERK1/2 and AKT phosphorylation showed alterations upon different treatments. Conclusions: Our findings show that Cetuximab-conjugated 90Y has a significant potential to eradicate human SCC cells. A combination of radioimmunotherapeutic compounds and external radiotherapy might be a promising treatment strategy for clinical application.